GREEN CHEMISTRY INNOVATIONS FOR A SUSTAINABLE FUTURE ADVANCES AND CHALLENGES – A REVIEW - Mohammad Yaqoob Sarfaraz (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2025)
Green chemistry has emerged as a revolutionary approach to addressing environmental issues by promoting sustainable and eco-friendly chemical processes. This paper critically reviews current advances in green chemistry, with a focus on renewable feedstocks, energy-efficient processes, and biodegradable products. The study examines contemporary literature, case studies, and technological innovations to provide a comprehensive overview of advancements in this field. Key studies highlight the effective implementation of green chemistry principles in industries such as pharmaceuticals, agriculture, and energy, leading to significant reductions in waste, toxic byproducts, and resource consumption. However, scalability, economic feasibility, and regulatory constraints remain major challenges. The findings suggest that, while green chemistry holds immense potential for sustainability, overcoming these limitations will require interdisciplinary collaboration, regulatory support, and continuous innovation. By integrating green chemistry into mainstream industrial practices, society can move closer to achieving global sustainability goals, reducing environmental harm, and fostering economic growth. This study underscores the importance of positioning green chemistry as a cornerstone of sustainable development and advocates for increased investment in research and education to accelerate global adoption.